Answer:
800000x^3
Step-by-step explanation:
Margin of error is 0.783985593816022
Answer:
![f'(x)=-\frac{2}{x^\frac{3}{2}}](https://tex.z-dn.net/?f=f%27%28x%29%3D-%5Cfrac%7B2%7D%7Bx%5E%5Cfrac%7B3%7D%7B2%7D%7D)
Step-by-step explanation:
So we have the function:
![f(x)=\frac{4}{\sqrt x}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7B4%7D%7B%5Csqrt%20x%7D)
And we want to find the derivative using the limit process.
The definition of a derivative as a limit is:
![\lim_{h \to 0} \frac{f(x+h)-f(x)}{h}](https://tex.z-dn.net/?f=%5Clim_%7Bh%20%5Cto%200%7D%20%5Cfrac%7Bf%28x%2Bh%29-f%28x%29%7D%7Bh%7D)
Therefore, our derivative would be:
![\lim_{h \to 0}\frac{\frac{4}{\sqrt{x+h}}-\frac{4}{\sqrt x}}{h}](https://tex.z-dn.net/?f=%5Clim_%7Bh%20%5Cto%200%7D%5Cfrac%7B%5Cfrac%7B4%7D%7B%5Csqrt%7Bx%2Bh%7D%7D-%5Cfrac%7B4%7D%7B%5Csqrt%20x%7D%7D%7Bh%7D)
First of all, let's factor out a 4 from the numerator and place it in front of our limit:
![=\lim_{h \to 0}\frac{4(\frac{1}{\sqrt{x+h}}-\frac{1}{\sqrt x})}{h}](https://tex.z-dn.net/?f=%3D%5Clim_%7Bh%20%5Cto%200%7D%5Cfrac%7B4%28%5Cfrac%7B1%7D%7B%5Csqrt%7Bx%2Bh%7D%7D-%5Cfrac%7B1%7D%7B%5Csqrt%20x%7D%29%7D%7Bh%7D)
Place the 4 in front:
![=4\lim_{h \to 0}\frac{\frac{1}{\sqrt{x+h}}-\frac{1}{\sqrt x}}{h}](https://tex.z-dn.net/?f=%3D4%5Clim_%7Bh%20%5Cto%200%7D%5Cfrac%7B%5Cfrac%7B1%7D%7B%5Csqrt%7Bx%2Bh%7D%7D-%5Cfrac%7B1%7D%7B%5Csqrt%20x%7D%7D%7Bh%7D)
Now, let's multiply everything by (√(x+h)(√(x))) to get rid of the fractions in the denominator. Therefore:
![=4\lim_{h \to 0}\frac{\frac{1}{\sqrt{x+h}}-\frac{1}{\sqrt x}}{h}(\frac{\sqrt{x+h}\sqrt x}{\sqrt{x+h}\sqrt x})](https://tex.z-dn.net/?f=%3D4%5Clim_%7Bh%20%5Cto%200%7D%5Cfrac%7B%5Cfrac%7B1%7D%7B%5Csqrt%7Bx%2Bh%7D%7D-%5Cfrac%7B1%7D%7B%5Csqrt%20x%7D%7D%7Bh%7D%28%5Cfrac%7B%5Csqrt%7Bx%2Bh%7D%5Csqrt%20x%7D%7B%5Csqrt%7Bx%2Bh%7D%5Csqrt%20x%7D%29)
Distribute:
![=4\lim_{h \to 0}\frac{({\sqrt{x+h}\sqrt x})\frac{1}{\sqrt{x+h}}-(\sqrt{x+h}\sqrt x)\frac{1}{\sqrt x}}{h({\sqrt{x+h}\sqrt x})}](https://tex.z-dn.net/?f=%3D4%5Clim_%7Bh%20%5Cto%200%7D%5Cfrac%7B%28%7B%5Csqrt%7Bx%2Bh%7D%5Csqrt%20x%7D%29%5Cfrac%7B1%7D%7B%5Csqrt%7Bx%2Bh%7D%7D-%28%5Csqrt%7Bx%2Bh%7D%5Csqrt%20x%29%5Cfrac%7B1%7D%7B%5Csqrt%20x%7D%7D%7Bh%28%7B%5Csqrt%7Bx%2Bh%7D%5Csqrt%20x%7D%29%7D)
Simplify: For the first term on the left, the √(x+h) cancels. For the term on the right, the (√(x)) cancel. Thus:
![=4 \lim_{h\to 0}\frac{\sqrt x-(\sqrt{x+h})}{h(\sqrt{x+h}\sqrt{x}) }](https://tex.z-dn.net/?f=%3D4%20%5Clim_%7Bh%5Cto%200%7D%5Cfrac%7B%5Csqrt%20x-%28%5Csqrt%7Bx%2Bh%7D%29%7D%7Bh%28%5Csqrt%7Bx%2Bh%7D%5Csqrt%7Bx%7D%29%20%7D)
Now, multiply both sides by the conjugate of the numerator. In other words, multiply by (√x + √(x+h)). Thus:
![= 4\lim_{h\to 0}\frac{\sqrt x-(\sqrt{x+h})}{h(\sqrt{x+h}\sqrt{x}) }(\frac{\sqrt x +\sqrt{x+h})}{\sqrt x +\sqrt{x+h})}](https://tex.z-dn.net/?f=%3D%204%5Clim_%7Bh%5Cto%200%7D%5Cfrac%7B%5Csqrt%20x-%28%5Csqrt%7Bx%2Bh%7D%29%7D%7Bh%28%5Csqrt%7Bx%2Bh%7D%5Csqrt%7Bx%7D%29%20%7D%28%5Cfrac%7B%5Csqrt%20x%20%2B%5Csqrt%7Bx%2Bh%7D%29%7D%7B%5Csqrt%20x%20%2B%5Csqrt%7Bx%2Bh%7D%29%7D)
The numerator will use the difference of two squares. Thus:
![=4 \lim_{h \to 0} \frac{x-(x+h)}{h(\sqrt{x+h}\sqrt x)(\sqrt x+\sqrt{x+h})}](https://tex.z-dn.net/?f=%3D4%20%5Clim_%7Bh%20%5Cto%200%7D%20%5Cfrac%7Bx-%28x%2Bh%29%7D%7Bh%28%5Csqrt%7Bx%2Bh%7D%5Csqrt%20x%29%28%5Csqrt%20x%2B%5Csqrt%7Bx%2Bh%7D%29%7D)
Simplify the numerator:
![=4 \lim_{h \to 0} \frac{x-x-h}{h(\sqrt{x+h}\sqrt x)(\sqrt x+\sqrt{x+h})}\\=4 \lim_{h \to 0} \frac{-h}{h(\sqrt{x+h}\sqrt x)(\sqrt x+\sqrt{x+h})}](https://tex.z-dn.net/?f=%3D4%20%5Clim_%7Bh%20%5Cto%200%7D%20%5Cfrac%7Bx-x-h%7D%7Bh%28%5Csqrt%7Bx%2Bh%7D%5Csqrt%20x%29%28%5Csqrt%20x%2B%5Csqrt%7Bx%2Bh%7D%29%7D%5C%5C%3D4%20%5Clim_%7Bh%20%5Cto%200%7D%20%5Cfrac%7B-h%7D%7Bh%28%5Csqrt%7Bx%2Bh%7D%5Csqrt%20x%29%28%5Csqrt%20x%2B%5Csqrt%7Bx%2Bh%7D%29%7D)
Both the numerator and denominator have a h. Cancel them:
![=4 \lim_{h \to 0} \frac{-1}{(\sqrt{x+h}\sqrt x)(\sqrt x+\sqrt{x+h})}](https://tex.z-dn.net/?f=%3D4%20%5Clim_%7Bh%20%5Cto%200%7D%20%5Cfrac%7B-1%7D%7B%28%5Csqrt%7Bx%2Bh%7D%5Csqrt%20x%29%28%5Csqrt%20x%2B%5Csqrt%7Bx%2Bh%7D%29%7D)
Now, substitute 0 for h. So:
![=4 ( \frac{-1}{(\sqrt{x+0}\sqrt x)(\sqrt x+\sqrt{x+0})})](https://tex.z-dn.net/?f=%3D4%20%28%20%5Cfrac%7B-1%7D%7B%28%5Csqrt%7Bx%2B0%7D%5Csqrt%20x%29%28%5Csqrt%20x%2B%5Csqrt%7Bx%2B0%7D%29%7D%29)
Simplify:
![=4( \frac{-1}{(\sqrt{x}\sqrt x)(\sqrt x+\sqrt{x})})](https://tex.z-dn.net/?f=%3D4%28%20%5Cfrac%7B-1%7D%7B%28%5Csqrt%7Bx%7D%5Csqrt%20x%29%28%5Csqrt%20x%2B%5Csqrt%7Bx%7D%29%7D%29)
(√x)(√x) is just x. (√x)+(√x) is just 2(√x). Therefore:
![=4( \frac{-1}{(x)(2\sqrt{x})})](https://tex.z-dn.net/?f=%3D4%28%20%5Cfrac%7B-1%7D%7B%28x%29%282%5Csqrt%7Bx%7D%29%7D%29)
Multiply across:
![= \frac{-4}{(2x\sqrt{x})}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B-4%7D%7B%282x%5Csqrt%7Bx%7D%29%7D)
Reduce. Change √x to x^(1/2). So:
![=-\frac{2}{x(x^{\frac{1}{2}})}](https://tex.z-dn.net/?f=%3D-%5Cfrac%7B2%7D%7Bx%28x%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%29%7D)
Add the exponents:
![=-\frac{2}{x^\frac{3}{2}}](https://tex.z-dn.net/?f=%3D-%5Cfrac%7B2%7D%7Bx%5E%5Cfrac%7B3%7D%7B2%7D%7D)
And we're done!
![f(x)=\frac{4}{\sqrt x}\\f'(x)=-\frac{2}{x^\frac{3}{2}}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7B4%7D%7B%5Csqrt%20x%7D%5C%5Cf%27%28x%29%3D-%5Cfrac%7B2%7D%7Bx%5E%5Cfrac%7B3%7D%7B2%7D%7D)
I would help you but the picture is blurry